2022
DOI: 10.3389/fmicb.2022.882419
|View full text |Cite
|
Sign up to set email alerts
|

Not All Liver Abscesses Are Created Equal: The Impact of Tylosin and Antibiotic Alternatives on Bovine Liver Abscess Microbial Communities and a First Look at Bacteroidetes-Dominated Communities

Abstract: Liver abscesses (LAs) are extremely prevalent in cattle and result in significant economic losses due to liver condemnation, decreased growth and production, and lower carcass quality. LAs are commonly attributed to the transition to diets high in rapidly fermentable starch which results in rumen epithelial inflammation that allows pathogenic bacteria to gain entry to liver through transport via the hepatic portal vein. The most common intervention for LAs is the inclusion of antibiotics in feedlot diets, unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…La presencia de abscesos destaca por ser la primera causa de decomiso en hígados de este estudio, confirmando los trabajos realizados por Sánchez (2013) y Pinnell et al (2022), producidos por Fusobacterium necroforum, Trueperella pyogenes y Salmonella entérica (Amachawadi et al, 2021).…”
Section: Discussionunclassified
“…La presencia de abscesos destaca por ser la primera causa de decomiso en hígados de este estudio, confirmando los trabajos realizados por Sánchez (2013) y Pinnell et al (2022), producidos por Fusobacterium necroforum, Trueperella pyogenes y Salmonella entérica (Amachawadi et al, 2021).…”
Section: Discussionunclassified
“…Beyond the impact on prior studies, it is important to understand the role of F. varium in the bovine rumen and whether or not it contributes to ruminal fermentation and LA occurrence and progression, or other disease processes. For several decades, ruminal F. necrophorum has been considered the primary etiological agent of liver abscesses, but recent studies have challenged this to varying extents, with data suggesting that Bacteroidetes and Proteobacteria may play a larger role than previously believed and that some LA communities may originate from the hindgut [53, 54]. Since most prior studies were conducted at genus-level taxonomic resolution (e.g., using 16S rRNA sequencing on an Illumina platform), it is currently unclear what role different Fusobacterium species may play in liver abscess formation and/or severity, and it cannot be ruled out that F. varium may play a direct or indirect role in LA formation.…”
Section: Discussionmentioning
confidence: 99%
“…F. necrophorum gained significant attention due to its ubiquitous presence in culture-based studies ( 50 , 52 , 53 ). In a recently comprehensive study, Whitlow and coauthors ( 54 ) reported significant abundance of Fusobacterium , Bacteroides , and Porphyromonas . And the discriminant genera for Fusobacteria-dominated abscess communities as Acinetobacter , Lactobacillus , Psdudomonas , and Psychrobacter .…”
Section: Methodsmentioning
confidence: 99%